Toward a general theory of luxury: Advancing from workbench definitions and theoretical transformations - Cristini, H.; Kauppinen-Räisänen, H.; Barthod-Prothade, M.; Woodside, Arch (Elsevier, 2017)
This study focuses on luxury, an intrinsic part of civilized society that historically reveals insights regarding the societal norms and mores. The perception of luxury is in a continuing state of flux due to the changing of many aspects of the economic market. This study takes a critical view on the transformations of luxury through the ages, examining the perception of luxury through historical, philosophical, and anthropological lenses. While the current views frequently equate luxury with the desire for the superfluous, driven by luxury brands and endorsed by celebrities, luxury has not always had that role in society. The study here contributes to the body of knowledge by providing a frame for understanding the transformation of luxury from being-to-having and owning, and to consumers' search for meaningfulness again via shifting from having-to-being and from owning-to-experiencing.